CO2 wettability of caprocks: Implications for structural storage capacity and containment security. Issue 21 (6th November 2015) - Iglauer, Stefan; Al‐Yaseri, Ahmed Zarzor; Rezaee, Reza; Lebedev, Maxim
Abstract: Structural trapping, the most important CO2 geostorage mechanism during the first decades of a sequestration project, hinges on the traditional assumption that the caprock is strongly water wet. However, this assumption has not yet been verified; and it is indeed not generally true as we demonstrate here. Instead, caprock can be weakly water wet or intermediate wet at typical storage conditions; and water wettability decreases with increasing pressure or temperature. Consequently, a lower storage capacity can be inferred for structural trapping in such cases. Key Points: Caprocks are intermediate wet or weakly water wet at typical storage conditions CO2 wettability increases with pressure and thus depth Structural storage capacities are significantly lower than previously predicted